Couper dans le cerveau pour le « fun » - Maxime Le Calvé (Revue d'anthropologie des connaissances)
How to prepare those aspiring to make a profession of cutting into a living human brain? In this article, I recount, drawing on “live” graphic field notes, the development of a neurosurgical simulation. This narrative is contextualised and theorised through a literature review on the anthropology of doing, the formation of habit, and the technologisation of skill transmission in surgery. This review allows me, along the way, to draw a parallel between the gestures of the neurosurgeon and the ethnographer, highlighting a shared poiesis between artistic, medical, and scientific practices, a concept already discussed by the poet Paul Valéry (1944). Through this inquiry, I join the practitioners in their attention to the ways in which they form their relationship with the physical matter they work with, and the possibility of building trust together through the “fun” of technical gesture.